2018
DOI: 10.1093/rheumatology/kex460
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of simple capillaroscopic definitions in describing capillary morphology in rheumatic diseases

Abstract: Reliability of simple capillaroscopic definitions in describing capillary morphology in rheumatic diseases Rheumatology key message. The optimized simple definitions for normal and abnormal capillary morphology provide excellent reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
6

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 6 publications
3
52
0
6
Order By: Relevance
“…The results of the report confirmed the conclusions of the earliest studies previously mentioned [40,41], namely that the capillaroscopy examination and its use in a homogeneous form can help in the correct interpretation of findings in daily practice.…”
Section: The Standardisation Of the Terminology In Nailfold Capillarosupporting
confidence: 84%
See 1 more Smart Citation
“…The results of the report confirmed the conclusions of the earliest studies previously mentioned [40,41], namely that the capillaroscopy examination and its use in a homogeneous form can help in the correct interpretation of findings in daily practice.…”
Section: The Standardisation Of the Terminology In Nailfold Capillarosupporting
confidence: 84%
“…Since one of the major problems in analysing and reporting the morphological changes observed by NVC in rheumatology is related to the need of a standardisation of the terminology, two consecutive recent studies reported on the reliability of simple capillaroscopic definitions in describing capillary morphology in rheumatic diseases [40,41].…”
Section: The Standardisation Of the Terminology In Nailfold Capillaromentioning
confidence: 99%
“…These simple definitions show high reliability, even in novices. 22,29 The morphological-functional correlation between capillaroscopic assessment and peripheral blood flow detection was also assessed. [30][31][32] The recent introduction of capillaroscopic assessment in the new EULAR/ACR classification criteria for SSc further confirmed its pivotal role in the diagnosis and management of the disease and suggested to search for automated systems of capillary counting.…”
mentioning
confidence: 99%
“…After the manual identification of the ROI, the system divided the ROI area into rectangles, obtained by checking the empty spaces between an alleged capillary and the next. Once their separation was achieved, rectangles were evaluated individually abnormal shape (a single-branched capillary in pathological conditions, ie, angiogenesis in SSc22,29 ).…”
mentioning
confidence: 99%
“…One problem is that the way to evaluate the NVC scleroderma spectrum abnormalities has not been integrated yet. Standardization regarding the findings of NVC has been proposed by the EULAR study group on microcirculation in Rheumatic diseases [16,17]. In general, qualitative interpretation of capillaroscopy can be applied (see scleroderma patterns by M Cutolo et al below) and quantitative interpretation is also being applied.…”
Section: Scoring Of Nvc Scleroderma Spectrum Abnormalities By Nvcmentioning
confidence: 99%